Rancang Bangun Double Ring Infiltrometer Untuk Pengukuran Pengaruh Penambahan Ketinggian Pasir - Muhammad Daffa; Mukhlis Ali (Universitas Nusa Putra, 2022)
Double ring infiltrometer is a tool to measure the rate of infiltration into the soil. The design of the double ring infiltrometer has 3 stages, the first using 304 stainless steel material, the next stage is the rolling process using a rolling machine 6 × 1300 mm BB613RL, and the last stage is the welding process using TIG welding. The effect of adding sand on changes in the infiltration rate that occurs in the two rings, in this change the slowing of the infiltration rate does occur because the sand blocks the infiltration of water directly into the soil. However, the slowdown in the infiltration rate that occurs tends to be very small so that it can be said that it has no significant effect on the infiltration rate without sand. The results of the measurements showed that the initial and constant infiltration rates slowed down with a change in the average infiltration rate that occurred, namely 0.005 mm/s at the initial infiltration rate and 0.002 mm/s at a constant infiltration rate. Thus it can be concluded that the addition of sand as a ground cover does not have much impact on the rate of water infiltration into the soil, especially in the direction of water infiltration perpendicular to the soil. So that this sand can be said to be a safe material to use as a ground cover compared to concrete, castings, or asphalt.